QUALITY ASSESSMENT OF WATER QUALITY IN IRAQI CITIES - Mansor, Maysoon; Kamel, Baraa T.; Jomaa’h, Muyasser M. (Journal of Applied Engineering Science, 2022)
The quality of drinking water directly affects human health and life. This study is concerned with the assessment of the drinking water quality in the main cities of 14 Iraqi governorates for the years 2011 and 2017 based on the Iraqi Central Statistical Organization statistical data for nine parameters. The Canadian method was used to calculate the Water Quality Index. The results showed a slight difference with the preference for water quality for the year 2011. The water quality is ranked excellent depending on the minimum values of statistical data, good based on the average value of statistical data, and poor depending on the maximum values of statistical data. The most influential parameters for the deviation of the water quality index values are sulphate and turbidity, and the lowest are the pH and electrical conductivity. The study showed that the water quality index does not give a consistent trend of the water quality change during the years 2011 and 2017. Therefore, the study recommends the use of other advanced statistical methods for this purpose. The study showed that the statistical data give less accurate results than the results of the tests, but it gives a clear initial picture for the decision-makers when the study area is wide and the research team is not available and the time period is long.